Extraction from Sweet Orange Peel (Citrus Aurantium var Sinesis), Lemongrass (Cymbopogon Citratus), and Jasmine (Jasminum sambac) as Aromatherapy Candles for Empowerment of Home Economics - Astrilia Damayanti; Hanif Ardhiansyah; Harianingsih Harianingsih; Ayasha Maharani; Rahimsyah Ijas Nur Rasyid; Salma Alfahra Choirunisa; Revasha Ajeng Kamalia; Ananda Muthi Athirah (Universitas Lambung Mangkurat, 2024)
The COVID-19 pandemic has affected the residents of Ngijo, a sub-district in Gunungpati District, Semarang. This community service activity aims to empower the Ngijo Family Welfare Development (PKK), Gunungpati, Semarang, as a solution for making aromatherapy candles from waste orange peel, jasmine flowers, and lemongrass. The methods of community service carried out include preparation, outreach, and evaluation. Preparations included signing a letter of cooperation with partners, making aromatherapy candles through six trials where the aroma smelled very good, and socializing with demonstrations where the team explained the consequences of product failure. Posters were given to residents to strengthen their understanding of this activity. The activity's success was seen in the residents' enthusiasm during the question-and-answer session regarding their understanding of making aromatherapy candles. The empowerment of PKK Ngijo, Gunungpati, and Semarang is successful because this activity is exciting and valuable, especially orange peel, which contains essential oils and has a refreshing aroma.